The Partij Akta Principle vs. Legal Precedent: How Divergent Interpretations in Indonesian Courts Create Uncertainty in Land Dispute Resolution - Nurbaedah; Hayeemaming, Marwan (NAJAHA, 2025)
Land disputes in Indonesia continue to pose significant challenges due to structural judicial inconsistencies, overlapping statutory and customary claims, and institutional weaknesses, generating legal uncertainty that undermines equitable land governance and social stability. This study critically examines doctrinal divergences between the Kediri District Court and East Java High Court decisions. It develops policy recommendations to harmonize procedural and substantive justice, including the potential integration of customary law into formal dispute resolution mechanisms. Using a qualitative doctrinal legal research design with descriptive-analytical methods, the study analyzes primary and secondary legal materials through documentary and content analysis, supported by comparative and interpretative approaches to contextualize judicial divergence within Indonesia's broader legal and social framework. The findings reveal a fundamental judicial divergence: the lower court emphasized substantive legal certainty based on prior rulings. In contrast, the appellate court prioritized procedural rigor under the Partij Akta principle, resulting in inconsistent outcomes despite identical factual circumstances. This contrast illustrates the structural tension between legal certainty and procedural fairness, highlighting systemic challenges in Indonesia’s civil law system. The study concludes that resolving land disputes requires an integrated approach combining judicial specialization, harmonized evidentiary standards, and coordinated institutional mechanisms to achieve predictable, equitable, and socially responsive governance. Academically, it offers a conceptual framework for understanding judicial divergence. At the same time, practically, it provides concrete recommendations, including specialized land courts, strengthened mediation pathways, and improved coordination between judicial and land administration bodies. Limitations include the focus on a limited number of cases and the doctrinal emphasis, which does not empirically track reform implementation. Future research should assess the effectiveness of proposed reforms, examine comparative cases in pluralistic legal systems, and explore long-term impacts on investment, social stability, and equitable land governance.